Detection of HPV in oral rinse samples from OPSCC and non-OPSCC patients. Issue 1 (December 2015) - Dang, Juliet; Feng, Qinghua; Eaton, Keith; Jang, Hona; Kiviat, Nancy
Abstract Background Due to the increasing rates of oropharyngeal cancer, oral HPV infection is a significant concern. Methods for detecting oral HPVs is not standardized as there are different techniques available. We propose that use of oral rinse samples to detect for HPVs is a suitable technique within a clinic setting. Thus, our main objective is to study HPV detection in oral rinse samples. Methods In our study, we used oral rinse sample collection coupled with real-time PCR to detect for HPVs types 16 and 18, and preferentially amplified FAP PCR samples to detect for a broad range of HPVs, in oropharyngeal squamous cell carcinoma (OPSCC), non-OPSCC, and healthy patients. Results Thirty three percent of 100 cancer patients were positive for any type of HPV; of those 23 were positive for HPV16. Only 1 of 110 healthy controls was positive (this subject was positive for HPV18). Conclusion Our results indicate that HPV detection in oral rinse samples may be useful as a screening tool to detect HPV-associated oral cancers.